2018
DOI: 10.1177/2054358118774536
|View full text |Cite
|
Sign up to set email alerts
|

Complete Hypokalemic Quadriparesis as a First Presentation of Sjögren Syndrome

Abstract: Rationale:We hope to increase awareness that hypokalemic paralysis may be the first presentation of Sjögren syndrome, for which potassium-sparing diuretics can be an effective adjunct to potassium replenishment.Presenting concerns:A 73-year-old female presented to a peripheral hospital with quadriparesis and a critically low serum potassium of 1.6 mmol/L with U waves on the electrocardiogram (ECG). The initial arterial blood gas showed a pH of 7.19, bicarbonate of 13 mEq/L, and a CO2 of 35 mm Hg. Over the next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…In extreme cases, Sjögren-related potassium wasting may lead to hypokalemic paralysis. 8 Our patient, although not paralyzed, was very weak on admission to hospital and had trouble walking, which most likely led to her fall.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In extreme cases, Sjögren-related potassium wasting may lead to hypokalemic paralysis. 8 Our patient, although not paralyzed, was very weak on admission to hospital and had trouble walking, which most likely led to her fall.…”
Section: Discussionmentioning
confidence: 72%
“…Amiloride and potassium citrate (which we used in our patient) have also been noted to be effective. 8 The neurologic manifestations of Sjögren syndrome are wide ranging. The peripheral nervous system may be affected in up to 25% of patients, 9 including sensory neuropathies of the limbs, cranial neuropathies and autonomic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Hypokalemic paralysis may precede sicca syndrome from 3 months to 4 years in the patient with final diagnosis of primary SS. Such cases have been initially diagnosed as RTA; some of these patients with hyperglobulinemia complained of dryness of the mouth and were later diagnosed as SS, while SS without hyperglobulinemia is rarely complicated by RTA [ 4 , 5 ]. In our patient, RTA appeared 5 years before the presentation of Sjögren's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports have been published in which hypokalemia secondary to this distal RTA, in some cases so profound as to lead to paralysis, as the initial presentation for SS. 8 Other renal manifestations can include mild isolated electrolyte disturbances, nephrolithiasis, immunoglobulin A nephropathy, membranous nephropathy, focal segmental glomerulosclerosis, immune complexmediated membranoproliferative glomerulonephritis, and a few case reports of crescentic glomerulonephritis. 2 Biopsy specimens from cohorts of patients with TIN secondary to primary SS have shown that interstitial infiltrates are composed predominantly of CD4þ T cells.…”
Section: Discussionmentioning
confidence: 99%